Development of A Critical Thinking Test with Science Content Oriented to Tri Hita Karana Local Wisdom - Suparya, I Ketut (Universitas Veteran Bangun Nusantara, 2024)
Critical thinking skills are essential for developing quality individuals, as mandated by Law No. 20 Year 2003. Effective learning should integrate material with the context of local wisdom. This study aims to design a valid and reliable critical thinking skills test incorporating science content oriented to Tri Hita Karana local wisdom for use in primary school education, particularly for fourth-grade students. This research adopts a development methodology based on the steps outlined by Borg and Gall. The process consists of seven stages, starting with research and information gathering and concluding with product revision. An extensive trial was conducted during the seventh stage to finalize a valid and reliable critical thinking skills test. The results indicate that the developed test, comprising 30 items, is both valid and reliable, with a reliability coefficient of 0.89, indicating a very high level of reliability. The study successfully created a critical thinking assessment tool that integrates science content with Tri Hita Karana local wisdom. In conclusion, this research contributes to the development of a robust critical thinking skills test for fourth-grade primary school students. By incorporating local wisdom, particularly Tri Hita Karana, into the learning process, the test promotes the integration of cultural context into education. This contribution is significant for enhancing the educational experience and fostering critical thinking among students.